(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The article provides information about information technology and systems of computer mathematics. The advantages of Mathcad and Maple are described in detail, as well as how to use these programs to solve differential equations. In addition, the article provides a number of suggestions and recommendations for mathematics teachers on the use of Mathcad and Maple in the educational process.